2016
DOI: 10.1149/2.0691609jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Liquid-Liquid-Solid Deposition of Ge at Hg Microdroplet Ultramicroelectrodes

Abstract: Individual Hg microdroplet electrodes were used to perform Ge electrochemical liquid-liquid-solid (ec-LLS) crystal growth in aqueous solutions containing dissolved GeO2. The Hg microdroplets were prepared by electrodeposition of Hg onto pre-existing Pt ultramicroelectrodes (r < 10 μm). These Hg microdroplet ultramicroelectrode platforms were then used for analyses of Ge ec-LLS by both voltammetry and amperometry. Voltammetric responses indicated that Ge was neither immediately nor quantitatively dissolved into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Using electrochemical gradients rather than thermal gradients, the electrochemical liquid–liquid–solid (ec-LLS) strategy mirrors the nucleation and crystal growth aspects of VLS and LPE but without any heating or extensive support apparatus. Simply, a liquid metal acts as the working electrode where oxidized species can be reduced and then dissolved into the liquid metal at rates dictated by the electrochemical reduction reaction, surface chemistry, and rates of dissolution. Recent studies have shown that the liquid metal alloy composition affects the resultant crystal size and morphology, , but clear design rules for the liquid metal have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Using electrochemical gradients rather than thermal gradients, the electrochemical liquid–liquid–solid (ec-LLS) strategy mirrors the nucleation and crystal growth aspects of VLS and LPE but without any heating or extensive support apparatus. Simply, a liquid metal acts as the working electrode where oxidized species can be reduced and then dissolved into the liquid metal at rates dictated by the electrochemical reduction reaction, surface chemistry, and rates of dissolution. Recent studies have shown that the liquid metal alloy composition affects the resultant crystal size and morphology, , but clear design rules for the liquid metal have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Prior electrochemical studies of Ge ec-LLS on Hg microdroplets support a complicated mechanism for the reduction of GeO 2 where adsorbed species may be involved. 57 If a rate-determining intermediate is surface bound and at too low of a surface coverage to result in the formation and dissolution of Ge 0 into the liquid metal, then Ge nanowire growth will not occur. The role of at least one surface-bound species in the electrochemical process is further in line with separate observation that Ge nanowire growth was never observed when the liquid metals were exposed to saturating levels of citrate ligands.…”
Section: Resultsmentioning
confidence: 99%
“…This point suggests that the formal concentration in solution did not directly relate to the rate of reduction (as would be expected for the reduction of a diffusion limited species in solution). Prior electrochemical studies of Ge ec-LLS on Hg microdroplets support a complicated mechanism for the reduction of GeO 2 where adsorbed species may be involved . If a rate-determining intermediate is surface bound and at too low of a surface coverage to result in the formation and dissolution of Ge 0 into the liquid metal, then Ge nanowire growth will not occur.…”
Section: Resultsmentioning
confidence: 99%
“…The basic observation that all of the e-BiIn caps had smooth shapes and surfaces devoid of Ge crystallites suggested that, under the conditions employed here, nucleation and crystallization of Ge at the e-BiIn/Si interface was energetically more favorable than homogeneously within e-BiIn and heterogeneously at the electrolyte/e-BiIn interface. Accordingly, we consider the solvation properties of e-BiIn for Ge more akin to Ga-based liquid metals , than pure Hg, where the former supports heterogeneous nano- and microwire growth while the latter does not. In this work, definitive evidence of epitaxial Ge micro- or nanowire growth was not collected.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously identified mercury (Hg), gallium (Ga), indium (In), and a eutectic alloy of Ga and In (e-GaIn) as metals that can operate as electrodes and growth solvents in ec-LLS. ,,, Metals without either Hg or Ga are particularly desirable since the former has high volatility and the latter tends to incorporate strongly in group IV semiconductor crystals . A potentially interesting alternative liquid metal is eutectic bismuth indium (21.3 at.…”
Section: Introductionmentioning
confidence: 99%